2022
DOI: 10.3390/foods11182801
|View full text |Cite
|
Sign up to set email alerts
|

Polymeric Compounds of Lingonberry Waste: Characterization of Antioxidant and Hypolipidemic Polysaccharides and Polyphenol-Polysaccharide Conjugates from Vaccinium vitis-idaea Press Cake

Abstract: Lingonberry (Vaccinium vitis-idaea L.) fruits are important Ericaceous berries to include in a healthy diet of the Northern Hemisphere as a source of bioactive phenolics. The waste generated by the V. vitis-idaea processing industry is hard-skinned press cake that can be a potential source of dietary fiber and has not been studied thus far. In this study, water-soluble polysaccharides of V. vitis-idaea press cake were isolated, separated, and purified by ion-exchange and size-exclusion chromatography. The resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 97 publications
0
7
0
Order By: Relevance
“…UV–visible absorption spectra can be used to investigate changes in the ultraviolet absorption of chromophores in amino acids and thus verify the mechanism of interaction between isovitexin and PL [49]. PL contains tyrosine, tryptophan, and phenylalanine, which gives it a maximum absorption wavelength of approximately 260 nm [50]. The absorption peak near 250–280 nm decreased with increasing concentration of isovitexin, and a red shift occurs near 260 nm (Figure 2 ) .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…UV–visible absorption spectra can be used to investigate changes in the ultraviolet absorption of chromophores in amino acids and thus verify the mechanism of interaction between isovitexin and PL [49]. PL contains tyrosine, tryptophan, and phenylalanine, which gives it a maximum absorption wavelength of approximately 260 nm [50]. The absorption peak near 250–280 nm decreased with increasing concentration of isovitexin, and a red shift occurs near 260 nm (Figure 2 ) .…”
Section: Resultsmentioning
confidence: 99%
“…PL contains tyrosine, tryptophan, and phenylalanine, which gives it a maximum absorption wavelength of approximately 260 nm [50]. The absorption peak near 250-280 nm decreased with increasing concentration of isovitexin, and a red shift occurs near 260 nm (Figure 2).…”
Section: Uv-visible Spectral Analysis Of Isovitexin and Plmentioning
confidence: 99%
“…In liver disorders various studies demonstrated and confirmed its anti-oxidative properties in different model of hepatitis resulting in obvious reduction in the hepatic fibrosis; on the other hand it could reduce hepatic stenosis [17][18][19].…”
Section: Introductionmentioning
confidence: 93%
“…Olennikov et al [83] extracted and purified different fractions of polysaccharide fractions from Vaccinium vitis-idaea (Lingonberry) waste. After further purification of the most antioxidant fraction, the authors found and described two distinct classes of polymers, with two representatives in each: (1) polyphenol-polysaccharide conjugates, with a neutral arabinogalactan backbone (suggested as linear 1-3-Galp with O-6 bound 1-3-Araf ) and hydroxycinnamoyl fragments (mainly sinapic and ferulic acids), and (2) mainly acidic pectin polysaccharides (1-4-GalpA).…”
Section: Polyphenols and Organic Acidsmentioning
confidence: 99%
“…After the conjugates performed much better in vitro on antioxidant potential for DPPH, ABTS, O 2 -and OH-, and had a better bile-acid-binding potential, they were administered to animals with standard and high-fat diets. While both polysaccharides were able to control animal body weight, TG, LDL-c, HDl-c, and total cholesterol levels, the polyphenol-polysaccharide conjugates were much more effective in controlling oxidative stress parameters, such as increasing liver antioxidant enzymes CAT, SOD, and glutathione peroxidase (GPX), and lowering serum MDA [83].…”
Section: Polyphenols and Organic Acidsmentioning
confidence: 99%